Quantum Dynamics and Laser Control for Photochemistry - Sala, Matthieu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The central subject of this thesis is the theoretical description of ultrafast dynamical processes in molecular systems of chemical interest and their control by laser pulses. This work encompasses different cutting-edge methods in quantum chemistry, quantum dynamics and for the rigorous description of the interaction of light and matter at the molecular level. It provides a general quantum mechanical framework for the description of chemical processes guided by laser pulses, in particular near conical intersections, i.e. geometries where the nuclear and electronic motions couple and the molecule undergoes non-adiabatic (or non-Born-Oppenheimer) dynamics. In close collaboration with experimentalists, the author succeeds in making a decisive step to link and to apply quantum physics to chemistry by transferring state of the art techniques and concepts developed in physics to chemistry, such as "light dressed atoms and molecules" and "adiabatic Floquet theory". He applies these techniques in three prototypic model systems (aniline, pyrazine and NHD2) using high-level electronic structure calculations. Readers will enjoy the comprehensive and accessible introduction to the topic and methodology, as well as the clear structure of the thesis.
Part I General introduction: Introduction -- Part II Theoretical studies in photophysics and photochemistry: applications to aniline and pyrazine: Basic concepts and methodology -- Exploration of the potential energy landscape of aniline using CASSCF and XMCQDPT2 electronic structure calculations -- Theory of nuclear quantum dynamics simulations -- The role of the low-lying nπ∗ states on the photophysics of pyrazine.-  Part III Laser control of unimolecular processes: Theoretical tools for the description of strong field laser-molecule interaction -- Laser control of the radiationless decay in pyrazine using the dynamic Stark effect -- Laser driven tunneling dynamics in NHD2.-  Part IV Conclusion: Conclusion.-  Appendices: A Basis sets for electronic structure calculations -- B Appendices for laser control of the radiationless decay in pyrazine using the dynamic Stark effect -- C Appendices for enhancement of tunneling in NHD2 -- D Appendices for thecoherent destruction of tunneling in NHD2.
Keywords: Chemistry, Physical and theoretical; Quantum physics; Chemometrics; Atoms; Molecules; Chemistry -- Data processing; Theoretical Chemistry; Quantum Physics; Mathematical Applications in Chemistry; Atoms and molecules in external fields; Computational Chemistry